NILAI INDEX WALKABILITY JALUR PEJALAN KAKI DI KAWASAN PERDAGANGAN DAN JASA KOTA SAMARINDA - Nugroho, Rizky Arif; Rusnabilah, Athaya (LPPM Universitas Terbuka, 2022)
Walking is one of the modes of transportation that can connect people from one place to another.Thus, it can be seen that walking is a mode of transportation that can connect human movement tomove from one place to another, especially in activity centers in urban areas in order to avoid trafficjams. Walking activities in activity centers in urban areas need to have the characteristics of aWalkable City. Walkable City is a city where residents in the city prefer to walk as the main mode oftransportation they use, for reasons of health, leisure, and improving the characteristics of the city inthe walkability index level. Based on this, it is necessary to know the value of the walkability index ofthe Pasar Pagi area of Samarinda City which is an area designated for trade and services with variouskinds of activities. The walkability index assessment is done by calculating the performance on eachwalkability index variable using a Likert Scale. The result is that based on the average value of thewalkability index of each road corridor, the walkability index value of the Morning Market Area is 36out of a maximum score of 100. This value means that the Morning Market Area is included in theNot Walkable category.